Office Examinations–Directed Treatment Paradigms Reduce Travel Burden, Decrease Treatment Cost, and Improve Quality-Adjusted Life-Years for Patients With Exudative Age-Related Macular Degeneration Undergoing Antivascular Endothelial Growth Factor Therapy. (November 2020) - Emerson, Geoffrey G.; Thompson, John T.; Vo, Loi V.; Mason, Robert W.H.; Lee, Gregory D.; Leder, Henry A.
Purpose: In the United States, most intravitreal injections are performed the same day as an office examinations; however, federal agencies and insurance payers suggest these same-day examinations charges are overused and have recommended scrutiny. In this study, we estimate the cost vs benefit to society of same-day office examinations during intravitreal injections for wet age-related macular degeneration (wAMD). Methods: An Excel spreadsheet was used to model different antivascular endothelial growth factor treatment scenarios for wAMD, including automatic treatment, injection series' treat and extend (T&E), and as-needed treatment, with increasing same-day examinations in the order listed. Treatment parameters were estimated using US population statistics, published literature, and Centers for Medicare & Medicaid Services, provider utilization data. Costs and benefits were compared for the 4 treatment scenarios. Results: Although yearly examinations and optical coherence tomography costs were higher for injection series, T&E, and as-needed protocols compared with automatic treatment, our model predicts reduced yearly injection and travel costs for those same treatment scenarios also, saving $2.9 billion (injection series), $7.2 billion (T&E), and $6.1 billion (as-needed) annually for the US population. Same-day injections accounted for 21%, 8%, and 9% of the savings, respectively, because of reduced travel burden. Furthermore, early detection of wAMD in the fellow eye during office examinations allows for a 1.8, 2.1, and 2.5 quality-adjusted life-year benefit, respectively. Conclusions: Office examinations–directed antivascular endothelial growth factor therapy for wAMD reduces travel and treatment expenses and improves screening of the fellow eye, resulting in robust cost savings and quality-adjusted life-year benefit for the US population.